GDF-15 is associated with sudden cardiac death due to incident myocardial infarction - Andersson, Jonas; Fall, Tove; Delicano, Rachel; Wennberg, Patrik; Jansson, Jan-Håkan (Resuscitation, 2020)
Aims: Preventing sudden cardiac death (SCD) due to acute myocardial infarction (MI) in previously healthy patients is challenging. Proteomic analysis may lead to an understanding of biological mechanisms and provide predictive biomarkers. Methods: In this prospective, nested case-control study from northern Sweden, 87 candidate cardiovascular protein biomarkers were studied in 244 individuals who later died within 24 h from an incident MI and 244 referents without MI and individually matched for age, sex and date of health examination and alive at the date of event in the index person. Association analysis was conducted using conditional logistic regression. Bonferroni correction was applied to avoid false positive findings. Results: Ten proteins were associated with future SCD due to acute MI in the non-adjusted analysis. The strongest association were found for growth differentiation factor 15 (GDF-15) with an odds ratio (OR) of 1.79 (95% confidence interval [CI] 1.41, 2.25) per standard deviation increase in protein, and urokinase-type plasminogen activator receptor with an OR of 1.66 (95% CI 1.34, 2.06). In models adjusted for lipid levels, body mass index, education, smoking, hypertension and C-reactive protein, only association with GDF-15 remained (OR 1.47 (95% 1.11, 1.95)). Conclusion: Elevated levels of GDF-15 are associated with increased risk of SCD within 24 h of incident MI. Further research may enable the use of GDF-15 together with other clinical and biological markers to guide primary preventive interventions for individuals at high risk for SCD.